Optimization of Energy Consumption in Cloud Computing Datacenters - Osman, Ahmed Osman (2018)
A Master of Science thesis in Computer Engineering by Ahmed Osman Osman entitled, “Optimization of Energy Consumption in Cloud Computing Datacenters”, submitted in June 2018. Thesis advisor is Dr. Assim Sagahyroon and thesis co-advisors are Dr. Fadi Aloul and Dr. Raafat Aburukba. Soft and hard copy available.